ANALISIS KECERDASAN EMOSIONAL SISWA TERHADAP KEMAMPUAN PROBLEM SOLVING MATEMATIKA SISWA SEKOLAH MENENGAH PERTAMA - Maftukhah, Nur Ajeng (Jurnal al Hikmah, 2018)
Emotional intelligence is one's ability to regulate emotions themselves. Emotional intelligence consists of self-awareness, self-regulation, motivation, empathy, social skills.If students are able to control their emotional intelligence, then all abilities will be controlled including problem solving abilities. Problem solving ability is the ability or effort used to find a solution to the problems faced. Emotional intelligence of students in junior high school is categorized as low and the level of emotional intelligence varies. Likewise, mathematical problem solving skills in junior high school students are still relatively low, students cannot think abstractly. Students' emotional intelligence is very influential on mathematical problem solving abilities.